2022
DOI: 10.1177/09567976221079633
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Resilience to Inflammation-Associated Depression: A Prospective Study of Breast-Cancer Survivors

Abstract: Stress can lead to depression, in part because of activation of inflammatory mechanisms. It is therefore critical to identify resilience factors that can buffer against these effects, but no research to date has evaluated whether psychosocial resilience mitigates the effects of stress on inflammation-associated depressive symptoms. We therefore examined psychosocial resources known to buffer against stress in a longitudinal study of women with breast cancer ( N = 187). Depressive symptoms and inflammation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In breast cancer survivors one year post-radiotherapy, both depressive symptoms and higher inflammatory markers were independent risk factors of fatigue; however, the correlation between depressive symptoms and inflammatory markers was not statistically significant 49 , 50 . CRP was positively associated with depressive symptoms only among women who reported high levels of cancer-related stress in a longitudinal study of women with breast cancer 51 . Inflammation was positively correlated with depressive symptoms only in women who also reported high level of anxiety, perceived stress, negative affect, or sleep disturbance 52 .…”
Section: Discussionmentioning
confidence: 92%
“…In breast cancer survivors one year post-radiotherapy, both depressive symptoms and higher inflammatory markers were independent risk factors of fatigue; however, the correlation between depressive symptoms and inflammatory markers was not statistically significant 49 , 50 . CRP was positively associated with depressive symptoms only among women who reported high levels of cancer-related stress in a longitudinal study of women with breast cancer 51 . Inflammation was positively correlated with depressive symptoms only in women who also reported high level of anxiety, perceived stress, negative affect, or sleep disturbance 52 .…”
Section: Discussionmentioning
confidence: 92%
“…This physiological process can assist the body in coping with systemic changes, such as in ammation and ischemia (34). Neuroin ammation and oxidative stress may mediate the pathogenesis of depression (35), and PUFAs show anti-in ammatory, anti-apoptotic, antioxidant, and neuroprotective properties; MUFAs also seem to reduce oxidative stress (36). IL-1, IL-6, and IFN-α can induce apoptosis and reduce neurogenesis, whereas PUFAs can reduce in ammation through lipoxygenase (LOX) and cytochrome P450 (CYP450) (37).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, resilience provides wide-ranging benefits when an individual faces challenging life events and suffering, such as severe illness. Interestingly, breast cancer survivors with higher resilience have been shown to exhibit weaker associations between stress and depressive symptoms, and weaker association between stress and inflammation-associated depressive symptoms, specifically [ 25 ]. The authors suggested that psychosocial resilience may play an important role in protecting individuals from inflammation-associated depressive symptoms under conditions of high stress [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, breast cancer survivors with higher resilience have been shown to exhibit weaker associations between stress and depressive symptoms, and weaker association between stress and inflammation-associated depressive symptoms, specifically [ 25 ]. The authors suggested that psychosocial resilience may play an important role in protecting individuals from inflammation-associated depressive symptoms under conditions of high stress [ 25 ]. In a biological level, psychosocial stressors have been shown to produce inflammation [ 44 ], which in turn elicits sickness behaviors that includes depressive symptoms [ 45 ]; likewise, resilience can be viewed as including complex processes that require integration of multiple central (such as hypothalamic–pituitary–adrenal-axis [HPA-axis]) and peripheral systems (such as immune system and gut microbiota) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation